Juran's quality control handbook - Juran, J. M. (Joseph M.), 1904-; Gryna, Frank M. (McGraw-Hill Book Company, 1988)
This desktop guide defines how to plan, produce, control and continually improve quality on a company-wide basis - from the executive suite to the factory floor. It makes extended use of authentic case studies to provide managers and executives with the quality control answers they need